Changing trends in disease burden of viral hepatitis B and its risk factors among Chinese residents from 1990 to 2019: an analysis of the Global Burden of Disease Study 2019 - Min ZHANG; Yuxiao ZHANG; Shanjiamei JIANG; Yali LIANG; Yue'e HUANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the changing trends of the disease burden of viral hepatitis B (HB) and its risk factors among Chinese residents from 1990 to 2019, to provide a reference for HB prevention and control. MethodsData on the disease burden of HB and its risk factors among Chinese residents from 1990 to 2019 were collected from the Global Burden of Disease Study 2019 (GBD 2019). Descriptive statistics were performed using standardized incidence, prevalence, mortality, and disability-adjusted life years (DALYs) rate of HB. Joinpoint regression model was used to analyze the trends of disease burden of HB attributable to smoking, alcohol consumption, drug abuse, and high body mass index (BMI) among Chinese residents from 1990 to 2019. ResultsDuring the 30-year period among Chinese residents there were significant decreasing trends in the HB standardized rate (1/100 000) of incidence (2 725.98 to 1 397.31), prevalence (12 239. 53 to 6 566.12), mortality (24.67 to 8.07), and DALYs (793.38 to 247.71), with average annual percentage changes (AAPC) of - 2.29%, - 2.13%, - 3.82%, and - 3.98%, respectively (P < 0.001 for all), and although declining more rapidly in a global comparison, these standardized rates were still higher than those in the total world population. The values of APPC were significantly higher negatively in the female population than in the male population for HB　standardized of incidence (- 2.49% vs. - 2.14%), prevalence (- 2.26% vs. - 2.04%), mortality (- 4.82% vs. - 3.48%), and DALYs (- 5.15% vs. - 3.63%) rates (all P < 0.001),　indicating that there was still a higher disease burden of HB in the male Chinese population. During this period, the standardized mortality rate and DALYs rate of HB attributable to smoking, drinking alcohol, drug use, and high BMI showed a significant decreasing trend (both P < 0.01), with the AAPC of - 62.20%, - 62.01%, - 44.44%, and - 18.18% for the mortality rate and - 63.90%, - 63.54%, - 47.71%, and - 18.76% for the DALYs rate. ConclusionAlthough the disease burden of viral hepatitis B among Chinese residents has decreased from 1990 to 2019, it is still higher than that of the world population, and male residents who smoke, consume alcohol, take drugs and have high body mass index still need to pay more attention.